Proline/arginine‐rich end leucine‐rich repeat protein N‐terminus is a novel osteoclast antagonist that counteracts bone loss. (19th August 2013) - Rucci, Nadia; Capulli, Mattia; Ventura, Luca; Angelucci, Adriano; Peruzzi, Barbara; Tillgren, Viveka; Muraca, Maurizio; Heinegård, Dick; Teti, Anna
ABSTRACT: hbd PRELP is a peptide corresponding to the N‐terminal heparin binding domain of the matrix protein proline/arginine‐rich end leucine‐rich repeat protein (PRELP). hbd PRELP inhibits osteoclastogenesis entering pre‐fusion osteoclasts through a chondroitin sulfate– and annexin 2–dependent mechanism and reducing the nuclear factor‐κB transcription factor activity. In this work, we hypothesized that hbd PRELP could have a pharmacological relevance, counteracting bone loss in a variety of in vivo models of bone diseases induced by exacerbated osteoclast activity. In healthy mice, we demonstrated that the peptide targeted the bone and increased trabecular bone mass over basal level. In mice treated with retinoic acid to induce an acute increase of osteoclast formation, the peptide consistently antagonized osteoclastogenesis and prevented the increase of the serum levels of the osteoclast‐specific marker tartrate‐resistant acid phosphatase. In ovariectomized mice, in which osteoclast activity was chronically enhanced by estrogen deficiency, hbd PRELP counteracted exacerbated osteoclast activity and bone loss. In mice carrying osteolytic bone metastases, in which osteoclastogenesis and bone resorption were enhanced by tumor cell–derived factors, hbd PRELP reduced the incidence of osteolytic lesions, both preventively and curatively, with mechanisms involving impaired tumor cell homing to bone and tumor growth in the bone microenvironment. Interestingly, in tumor‐bearing mice, hbd PRELP also inhibited breast tumor growth in orthotopic sites and development of metastatic disease in visceral organs, reducing cachexia and improving survival especially when administered preventively. hbd PRELP was retained in the tumor tissue and appeared to affect tumor growth by interacting with the microenvironment rather than by directly affecting the tumor cells. Because safety studies and high‐dose treatments revealed no adverse effects, hbd PRELP could be employed as a novel biological agent to combat experimentally induced bone loss and breast cancer metastases, with a potential translational impact.